The Influence of Leadership and Work Environment on the Performance of Personnel at Korem 031/WB Pekanbaru - Yan Horas Simanjuntak; Asep Kurniawan (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
This study has a problem formulation of how the influence of leadership and work environment affects the performance of personnel at Korem 031/WB especially the personnel of Makorem 031/WB with the aim of knowing the magnitude of the influence of leadership and work environment on the performance of personnel at Korem 031/WB, especially personnel of Makorem 031/ WB. This research method uses quantitative methods with analytical testing techniques using simple linear regression, t test, f test and the coefficient of determination. The results of this study indicate that the leadership variable has an influence on personnel performance by 58% and the work environment variable has a positive influence as well as 54%. Simultaneously leadership and work environment on the performance of personnel have a positive effect. So the results of the study are in line with the hypothesis that there is an influence between leadership and work environment on the performance of personnel at Makorem 031/WB.